2015
DOI: 10.1152/ajpendo.00396.2014
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated changes in hepatic amino acid metabolism and endocrine signals support hepatic glucose production during fetal hypoglycemia

Abstract: Houin SS, Rozance PJ, Brown LD, Hay WW Jr, Wilkening RB, Thorn SR. Coordinated changes in hepatic amino acid metabolism and endocrine signals support hepatic glucose production during fetal hypoglycemia. Am J Physiol Endocrinol Metab 308: E306 -E314, 2015. First published December 17, 2014 doi:10.1152/ajpendo.00396.2014.-Reduced fetal glucose supply, induced experimentally or as a result of placental insufficiency, produces an early activation of fetal glucose production. The mechanisms and substrates used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
3
31
1
1
Order By: Relevance
“…These results show that fetal anemic hypoxemia is sufficient to stimulate and sustain increases in factors that are associated with activation of both gluconeogenesis and glycogenolysis. Furthermore, these results demonstrate that fetal hypoglycemia (a hallmark of PI-IUGR) is not necessary for this response, even though it can, by itself, lead to fetal HGP (21). Supporting this conclusion is our finding that exposure to either 3% oxygen or glucogenic activators (cAMP ϩ dexamethasone) increases expression of PCK1 and PGC1A in isolated fetal hepatocytes.…”
Section: Discussionsupporting
confidence: 64%
“…These results show that fetal anemic hypoxemia is sufficient to stimulate and sustain increases in factors that are associated with activation of both gluconeogenesis and glycogenolysis. Furthermore, these results demonstrate that fetal hypoglycemia (a hallmark of PI-IUGR) is not necessary for this response, even though it can, by itself, lead to fetal HGP (21). Supporting this conclusion is our finding that exposure to either 3% oxygen or glucogenic activators (cAMP ϩ dexamethasone) increases expression of PCK1 and PGC1A in isolated fetal hepatocytes.…”
Section: Discussionsupporting
confidence: 64%
“…It is delivered to the fetus by facilitated diffusion across the placenta according to its maternal-fetal concentration gradient (Hay et al, 1990), eliminating the need for endogenous hepatic glucose production (HGP) by the fetus (Hay et al, 1984). Indeed, studies using catheters across the liver in normal fetal sheep have shown that there is net hepatic glucose uptake, rather than hepatic glucose output (Houin et al, 2015, Teng et al, 2002, Timmerman et al, 2000). The absence of fetal hepatic glucose output is advantageous for the fetus as it helps maintain the maternal-fetal glucose concentration gradient and transfer of maternally derived glucose to the fetus (Thureen et al, 1992).…”
Section: Early Activation Of Hepatic Glucose Production In Iugr Fetusmentioning
confidence: 99%
“…Similar to the IUGR fetus, the hypoglycemic fetus increases fetal HGP and hepatic gluconeogenic gene activation (DiGiacomo and Hay, 1989, DiGiacomo and Hay, 1990, Fowden and Forhead, 2012, Hay et al, 1981, Narkewicz et al, 1993, Rozance et al, 2008, Thorn et al, 2012). Acute hypoglycemia can also activate HGP, as HGP has been directly measured using hepatic catheterization as evidenced by net hepatic glucose output, rather than uptake, following hypoglycemia for 4 d (Houin et al, 2015). …”
Section: Mechanisms For the Early Activation Of Fetal Hgp In The Imentioning
confidence: 99%
“…Thus it seems that mobilization of glycogen is a key mechanism that contributes to the short-term fetal glucose regulation. On the other hand, gluconeogenesis, regulated by glucagon, does not play a signifi cant part in fetal glucose homeostasis, although such a mechanism would be possible due to the large increase in amino acid catabolism observed during prolonged fasting [100].…”
Section: Carbohydrate Metabolism and Energy Homeostasismentioning
confidence: 99%